The relevance of feminism in promoting gender reform in the context of progressive Islam - Karimullah, Suud Sarim; Nugraha, Aat Ruchiat; Nisa’, Ihda Shofiyatun; Andini, Yokke (Pusat Studi Gender dan Anak, 2023)
This study investigates the significance of feminism in promoting gender reform in the context of progressive Islam, using library research with a holistic literature analysis. Through careful review and comprehensive synthesis of related literature, the study aims to understand the evolution of the concept of feminism in progressive Islam as well as its impact on gender reform efforts. The results confirm that gender equality in progressive Islam can strengthen the feminist movement by providing a solid foundation for inclusive social change. The positive impact of the feminist movement in this context is evident through the changes that have taken place, especially in the empowerment of women and the increase in public awareness of gender issues. However, challenges, including resistance from conservative groups and solid social norms, suggest that gender reform is a long journey that requires sustained commitment and solid cooperation from various parties. In addition, the importance of the role of youth, inclusive education, supportive legal and policy changes, and active community participation are critical factors in achieving greater gender equality in a diverse Muslim community.